Gemcitabine Maintenance Therapy in Patients With Metastasized Soft Tissue Sarcomas - Harrer, Dennis Christoph; Buschauer, Sebastian; Sterz, Ulrich; Menhart, Karin; Wendl, Christina; Heudobler, Daniel; Grube, Matthias; Pukrop, Tobias; Herr, Wolfgang; Vogelhuber, Martin (Frontiers in Oncology, 2021)
Background Metastasized soft-tissue sarcomas still pose a significant therapeutic challenge given the limited efficacy of currently available multimodal treatment strategies. Recent progress in molecular characterization of sarcoma subtypes has enabled successful personalized therapy approaches in a minority of selected patients with targetable mutations. However, in the majority of patients with refractory soft tissue sarcomas, long-term survival remains poor. Methods We report on three adult patients with various soft tissue sarcomas subjected to Gemcitabine maintenance therapy. Tumor entities included leiomyosarcoma of the pancreas (patient 1), undifferentiated pleomorphic sarcoma of the right femur (patient 2), and peri-aortic leiomyosarcoma (patient 3). Metastatic sites encompassed liver, lung, and bones. All patients received Gemcitabine maintenance therapy until disease progression following prior salvage chemotherapy with Docetaxel and Gemcitabine. Patients were treated outside of clinical trials. Response assessment was based on radiological imaging. Results In response to salvage chemotherapy with Docetaxel and Gemcitabine, one patient exhibited a partial remission, and two patients showed stable disease. Patient 1 exhibited stable disease for 6 months during Gemcitabine maintenance therapy before suffering rapid progression of hepatic metastases. Patient 2 underwent 21 months of Gemcitabine maintenance therapy, which was discontinued after progressive pulmonary metastases were detected. Patient 3 is still being treated with Gemcitabine maintenance therapy. Remarkably, owing to significant chemotherapy-associated hematotoxicity, the dose of Gemcitabine dose was reduced by two-thirds. Nevertheless, stable disease with constant pulmonary metastases has been maintained in this patient for 14 months. Conclusions Gemcitabine maintenance therapy following prior Docetaxel and Gemcitabine chemotherapy is manageable and reveals potential benefits for patients with aggressive metastasized soft tissue sarcomas. Prospective trials evaluating Gemcitabine maintenance therapy are encouraged.